KONDISI SOSIAL EKONOMI NELAYAN DI NAGARI KACANG KECAMATAN X KOTO SINGKARAK KABUPATEN SOLOK - Rizandi Hidayat; Afdhal Afdhal (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims to find out (1) how is the condition of fishermen's education, (2) how is the condition of the fishermen's residence and (3) how is the condition of fishermen's expenses. This study generally aims to determine the socio-economic conditions of fishermen in Nagari Kacang, X Koto Singkarak District. The type of research used is descriptive quantitative research. The population in this study were all fishermen in Nagari Kacang, X Koto Singkarak district, Solok district. Determination of the sample using a total sampling technique. The source of this research data comes directly from fishermen. Data collection techniques used are questionnaires and documentation. The results of this study indicate that: (1) the education level of fishermen in Nagari Kacang is on average only junior high school graduates, (2) while the education level of fishermen's children is on average high school graduates, (3) for the condition of the houses occupied by fishermen on average is a permanent house (privately owned) with a floor made of concrete (cement), (4) the next for expenditures in the form of food issued by the fishermen's village on average is in the range of Rp. 786.000 – Rp. 1.108.0000, (5) while non-food expenditures issued by fishermen's families for one month are in the Rp. 795,000 – Rp. 1,793,000. It can be concluded that the more family members there are in one house, the greater the expenses that will be issued.